The effect of corporate taxation on bank transparency: Evidence from loan loss provisions - Andries, Kathleen; Gallemore, John; Jacob, Martin (Journal of Accounting and Economics, 2017)
We examine how the corporate tax system, through its treatment of loan losses, affects bank financial reporting. Exploiting cross-country and intertemporal variation in income tax rates and loan loss provision deductibility, we find that loan loss provisions are increasing in the tax rate for countries that permit general provision tax deductibility. When general provisions are deductible, a 1 percentage point rate increase leads to a provision increase of 4.9% of the sample average. This effect is driven by the tax system's encouragement of timelier loan loss recognition, suggesting that corporate taxation is an important determinant of bank financial reporting transparency.